Computational study of Capturing CO2 and SO2 gases using imidazolium based ionic liquids - Awoke, M G (Bangladesh Journal of Scientific and Industrial Research, 2024)
The objective of this study was to capture toxic gases like CO2 and SO2 using imidazolium based ionic liquids,1-butyl 3-methyl-imidazoliumbis(trifluoromethylsulfonyl)imide) and 1-ethyl 3-methyl-imidazolium acetate. In this work, the density functional theory (DFT) method of hybrid correlation functional with B3LYP/6-31++G (d, p) basis set was used to analyze the mechanism of interaction between toxic gases and ionic liquids. It has been founded that the [Bmim][Tf2N]-SO2 has greater binding energy than [Bmim][Tf2N]-CO2 . Therefore, the ionic liquid [Bmim][Tf2N] seems to be the most suitable option for SO2 gas capture. Similarly, The ionic liquid [Emim][Ac] has high efficiency to capture the toxic gas SO2 and has high affinity for this gas relative to CO2. The types of absorption observed in [Bmim][Tf2N]-SO2 interaction was Chemisorption while, [Bmim]Tf2N]-CO2 interaction was physisorption. To sum up, [Bmim][Tf2N] and [Emim][Ac] seems to be the most suitable option and has high efficiency to capture SO2 gas relative to CO2. Bangladesh J. Sci. Ind. Res. 59(2), 73-86, 2024